Melicope iolensis (Rutaceae), a new tree species from Kaua‘i, Hawaiian Islands - Kenneth R. Wood; David H. Lorence; Warren L. Wagner; Marc S. Appelhans (PhytoKeys, 2024)
A newly-discovered endemic tree species of Melicope from Kaua‘i, Hawaiian Islands, is described and illustrated with notes on its distribution, ecology, conservation status and phylogenetic placement. A modification to the existing key to Hawaiian Melicope is also provided. Melicope iolensis sp. nov. is a member of Stone’s Megacarpa group having carpels connate at base, capsules 4-lobed and leaves usually opposite. The new species differs from its Hawaiian congeners by its unique combination of abaxially glabrate to pilose-pubescent leaves with petioles up to 70 mm long, ramiflorous and axillary inflorescences, sepals on staminate flowers 0.3–0.5 mm long, capsules with green and purple streaking, 10–14 mm wide and seeds 3–3.5 mm long. Since its discovery in 2021, 15 individuals have been documented within a single remote windward hanging valley below the Kawaikini Summit of Kaua‘i. Melicope iolensis represents a new Critically Endangered (CR) single island endemic species in need of conservation.